Zirconium–Porphyrin‐Based Metal–Organic Framework Hollow Nanotubes for Immobilization of Noble‐Metal Single Atoms - He, Ting; Chen, Shuangming; Ni, Bing; Gong, Yue; Wu, Zhao; Song, Li; Gu, Lin; Hu, Wenping; Wang, Xun (Angewandte Chemie International Edition, 2018)
Single atoms immobilized on metal–organic frameworks (MOFs) with unique nanostructures have drawn tremendous attention in the application of catalysis but remain a great challenge. Various single noble‐metal atoms have now been successfully anchored on the well‐defined anchoring sites of the zirconium porphyrin MOF hollow nanotubes, which are probed by aberration‐corrected scanning transmission electron microscopy and synchrotron‐radiation‐based X‐ray absorption fine‐structure spectroscopy. Owing to the hollow structure and excellent photoelectrochemical performance, the HNTM‐Ir/Pt exhibits outstanding catalytic activity in the visible‐light photocatalytic H2 evolution via water splitting. The single atom immobilized on MOFs with hollow structures are expected to pave the way to expand the potential applications of MOFs. Single noble metal atoms can be successfully immobilized on the well‐defined anchoring sites of zirconium–porphyrin MOF hollow nanotubes. Owing to the hollow structure and excellent photoelectrochemical performance, HNTM‐Ir/Pt exhibits outstanding catalytic activity in the visible‐light photocatalytic H2 evolution via water splitting.